HABITAT CHARACTERISTICS OF HOOLOCK GIBBON (Hoolock hoolock (HARLAN, 1834)) IN AND AROUND INNER-LINE RESERVE FOREST, CACHAR, BARAK VALLEY, SOUTHERN ASSAM, INDIA - ISLAM, MOFIDUL; CHOUDHURY, PARTHANKAR; BHATTACHARJEE, PARIMAL CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Hoolock gibbons (Hoolock hoolock Harlan, 1834) are endangered (A4acd ver3.1) small apes occurring in Bangladesh, India, Myanmar, and south China. In India they only occur in the north eastern states. The Inner-line reserve forest of Barak Valley is one of the habitat of Hoolock gibbon where these gibbon groups were surveyed and habitat assessment was done. The gibbon population was estimated by the modified line-transect method [1,2] and the direct count method. Following Kumar et al. (2009)[3], the line transects were laid in a stratified random design to cover all selected areas in the forest. During the survey period 33 individuals (9 groups and one solitary individual) were encountered from 10 different forest patches in the Inner-line reserve forest and its adjoining areas. Strip sampling was done to assess the habitat characteristics of the gibbon groups. A total of 143 tree species belonging to 45 families were identified with their Importance Value Index (IVI) value in the 10 representative sites of the study area. Average canopy cover (%), tree height (m) and tree DBH (≥10cm) were found to be 55.95±1.8, 19.2±0.95 and 23±0.98 respectively. Artocarpus chama Buch- Ham., Syzygium cumini L., Diospyras taposia Ham., Dysoxylum gobora Miq., Toona ciliata M. Roem., Chrysophyllum roxburghii G.Don . were the tree species having the highest IVI value in the gibbon habitat. Principal component analysis (PCA) showed that the gibbon habitat is highly correlated with tree canopy cover, tree abundance and food tree abundance in the study site.